Efektivitas Fitur ChatGPT, Gemini dan Claude AI dalam Membantu Guru Membuat Bahan Ajar - Muttaqin Kholis Ali; Al Muhtadibillah Ali; Arrahmil Hasanah (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the effectiveness of the features of ChatGPT, Gemini AI, and Claude AI in helping teachers create teaching materials at SMA Negeri 1 Tambangan. This study uses an experimental design of participants who are divided into four groups (three AI groups and one control group), this study compares the quality of the teaching materials produced with the help of the three AI platforms. Data collection methods include pre-test, post-test, questionnaire, and analysis of AI usage activity logs. The results of the analysis show that Gemini AI has better results in improving the quality of teaching materials, with an average score increase of 20.5 points, compared to ChatGPT (13.4 points) and Claude AI (14.6 points). Gemini AI's advantages are mainly seen in the aspects of contextualization and personalization of learning materials. The results of the technology acceptance analysis show that the adoption rate is high for Gemini AI, with the highest scores in perceived usefulness (6.4/7) and behavioral intention (6.6/7). Implementation challenges include the need for teacher training and limited infrastructure in several regions. This research provides important implications for the development of policies and practices for the use of AI in education in Indonesia, emphasizing the importance of integrating AI technology that takes into account the local context and specific needs of students.